2017
DOI: 10.1101/165761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A parametric texture model based on deep convolutional features closely matches texture appearance for humans

Abstract: Our visual environment is full of texture-"stuff" like cloth, bark or gravel as distinct from "things" like dresses, trees or paths-and humans are adept at perceiving subtle variations in material properties. To investigate image features important for texture perception, we psychophysically compare a recent parameteric model of texture appearance (CNN model) that uses the features encoded by a deep convolutional neural network with two other models: the venerable Portilla and Simoncelli model (PS) and an ext… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 84 publications
(86 reference statements)
0
24
0
Order By: Relevance
“…The current work was motivated by the broad scientific goal of discovering models that quantitatively explain the neuronal mechanisms underlying primate invariant object recognition behavior. To this end, previous work had shown that specific artificial neural network models (ANNs), drawn from a large family of deep convolutional neural networks (DCNNs) and optimized to achieve high levels of object categorization performance on large-scale image-sets, capture a large fraction of the variance in primate visual recognition behaviors (Rajalingham et al, 2015; Jozwik et al, 2016; Kheradpisheh et al, 2016; Kubilius et al, 2016; Peterson et al, 2016; Wallis et al, 2017), and the internal hidden neurons of those same models also predict a large fraction of the image-driven response variance of brain activity at multiple stages of the primate ventral visual stream (Yamins et al, 2013; Cadieu et al, 2014; Khaligh-Razavi and Kriegeskorte, 2014; Yamins et al, 2014; Güçlü and van Gerven, 2015; Cichy et al, 2016; Hong et al, 2016; Seibert et al, 2016; Cadena et al, 2017; Wen et al, 2017). For clarity, we here referred to this sub-family of models as DCNN IC (to denote ImageNet-Categorization training), so as to distinguish them from all possible models in the DCNN family, and more broadly, from the super-family of all ANNs.…”
Section: Discussionmentioning
confidence: 99%
“…The current work was motivated by the broad scientific goal of discovering models that quantitatively explain the neuronal mechanisms underlying primate invariant object recognition behavior. To this end, previous work had shown that specific artificial neural network models (ANNs), drawn from a large family of deep convolutional neural networks (DCNNs) and optimized to achieve high levels of object categorization performance on large-scale image-sets, capture a large fraction of the variance in primate visual recognition behaviors (Rajalingham et al, 2015; Jozwik et al, 2016; Kheradpisheh et al, 2016; Kubilius et al, 2016; Peterson et al, 2016; Wallis et al, 2017), and the internal hidden neurons of those same models also predict a large fraction of the image-driven response variance of brain activity at multiple stages of the primate ventral visual stream (Yamins et al, 2013; Cadieu et al, 2014; Khaligh-Razavi and Kriegeskorte, 2014; Yamins et al, 2014; Güçlü and van Gerven, 2015; Cichy et al, 2016; Hong et al, 2016; Seibert et al, 2016; Cadena et al, 2017; Wen et al, 2017). For clarity, we here referred to this sub-family of models as DCNN IC (to denote ImageNet-Categorization training), so as to distinguish them from all possible models in the DCNN family, and more broadly, from the super-family of all ANNs.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore believe that our approach is complementary to the local approach taken by studies that investigated texture processing (e.g. Freeman & Simoncelli, 2011;Gerhard et al, 2013;Wallis et al, 2016Wallis et al, , 2017 Pixels Fourier Latent Image domain 1 0 1 2 Discriminability d Figure 7: Turns in other image spaces are harder to detect Average sensitivity for detecting a 90-degree turn in an image sequence along a path through pixel space, through Fourier space, and through latent space. Error bars mark 95% confidence intervals and gray dots mark performance of individual observers.…”
Section: Global Vs Local Image Modelsmentioning
confidence: 98%
“…Our images were only 32×32 pixels in size. In contrast, Wallis et al (2017) used image patches that were 128×128 pixels to compare between texture images created from a deep neural network model and real photographs of textures. Other studies have used a range of images sizes (Alam et al, 2014;Sebastian et al, 2017;Bex, 2010, in increasing order of image size), but our images are closer to the range of image sizes used as patches of images (Gerhard et al, 2013) rather than entire images.…”
Section: Small Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…We further investigated a tumor-related region around the PCa to extract deep learning-embedded features. The deep learningembedded features adopted a transfer learning technique based on a VGG-19 networks which is pretrained on ImageNet 28 . For each case, the axis-slice with largest area of the PCa cross section was selected from axial T 2 WI, high-b DWI and ADC images.…”
Section: Radiomics Features Including Shapesmentioning
confidence: 99%